Anti-corrosion performances of hybrid silane coatings on AZ31 alloy. Issue 3 (29th May 2018) - Calabrese, Luigi; Caprì, Angela; Proverbio, Edoardo
Abstract : Purpose: This paper aims to evaluate the efficacy of a zeolite-filled silane sol–gel coating as protective layer on pretreated AZ31 magnesium alloy substrates. Design/methodology/approach: Anti-corrosion properties of a silane–zeolite composite coating, at various zeolite content, have been investigated on AZ31 magnesium substrates subjected to different surface pretreatment procedures before coating deposition. A short time etching by hydrofluoric acid (HF) and an anodic polarization in NaOH solution were used as surface pretreatments. Findings: High hydrophobicity and good adhesion performances of coatings have been observed. Corrosion protection performance, during immersion in 3.5 per cent NaCl solution, was evaluated by means of electrochemical impedance spectroscopy tests. All coating formulations evidenced good barrier properties. Better durability properties have been shown by coating obtained on HF pretreated magnesium substrate and with a 60 per cent of zeolite content. Originality/value: High electrochemical reactivity of magnesium alloys represents the mayor limit of its application in many different fields. In this concern, zeolite-based coatings are emerging as potentially effective environmentally friendly coating for metallic substrates. Despite aluminum and stainless steel substrates, in the literature, only expensive direct synthesis zeolite coating was investigated for its application on magnesium alloys protection. For this reason, this paper fulfills the need to assess the adhesion and anti-corrosion behavior of sol–gel silane–zeolite coating in magnesium alloy substrates.